2011
DOI: 10.5539/ijbm.v6n5p156
|View full text |Cite
|
Sign up to set email alerts
|

Nigeria’s External Debt and Economic Growth: An Error Correction Approach

Abstract: This study investigates the relationship between Nigeria's external debt and economic growth, between 1975 and 2006. The choice of period was guided by data availability and the the escalation of Nigeria's external debt. Econometric evidence revealed stationarity of the variables at their first difference while the Johansen cointegration approach also confirms the existence of one cointegrating relationship at the 1 percent and 5 percent level of significance. In addition, error correction estimates revealed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 16 publications
3
25
0
Order By: Relevance
“…This result aligns with Obademi (2013) and Vincent, Hamilton and Joseph (2011). The short run error correction model which shows a negative relationship between external debt and economic growth in Nigeria is in tandem with Mayowa and Aigbedo (2012).…”
Section: Discussion Of Findingssupporting
confidence: 66%
“…This result aligns with Obademi (2013) and Vincent, Hamilton and Joseph (2011). The short run error correction model which shows a negative relationship between external debt and economic growth in Nigeria is in tandem with Mayowa and Aigbedo (2012).…”
Section: Discussion Of Findingssupporting
confidence: 66%
“…Debt payment to Paris Club creditors and debt payment to promissory notes holders/are positively related to GDP and GFCF, while debt payment to London Club creditors and other creditors showed a negative significant relation to GDP and GFCF. Ezeabasili, Isu, and Mojekwu, (2011) investigated the relationship between Nigeria's external debt and economic growth between 1975 and 2006 applying econometric analyses. The result of the error correction estimates revealed that external-debt has negative relationship with economic growth in Nigeria.…”
Section: Empirical Literaturementioning
confidence: 99%
“…The result showed that external debt has contributed positively to Nigeria economy. This was supported by Ezeabasili, Isu, and Mojekwu, (2011) who examine the relationship between Nigeria"s external debt and economic growth between1975-2006, with an error correction approach. Error correction estimate revealed that external debt has negative relationship with economic growth in Nigeria.…”
Section: Empirical Reviewmentioning
confidence: 91%